Tekanan Stakeholder dan Ukuran Perusahaan pada Sustainability Report - Darmawan, Bagus Adya; Sudana, I Putu (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p08, 2022)
The research aims to determine the effect of stakeholder pressure and company size on the Sustainability Report. The research was conducted at the Indonesia Stock Exchange (IDX) using the 2017-2020 research period. The population in the research is all companies listed on the IDX in 2017-2020 which issued Sustainability Reports and used the GRI Standards. The number of samples used were 84 observations. In this research using non-probability sampling method with purposive sampling technique. Research using multiple linear analysis. The research results show that environmental pressure and company size have a positive effect on Sustainability Report, employee pressure and shareholder pressure have no effect on Sustainability Report and consumer pressure has a negative effect on Sustainability Report. Keywords: Sustainability Report; Stakeholder Pressure; Company Size.